The Post-crisis Narrowing of International Imbalances Cyclical or Durable? - Ollivaud, Patrice (OECD Publishing, 2013)
After peaking in the first half of 2008, international imbalances declined sharply during the global crisis of 2008-09, in part reflecting cyclical factors such as large contractions in domestic demand on the back of bursting housing bubbles in a number of deficit countries, as well as large declines in cross-border capital flows, interest rates and commodity prices. This paper suggests that business and housing cycles alone account for around half of the decline in international imbalances, with real exchange rate and fiscal adjustments explaining only around one fifth. A range of stylised scenarios for the major trading areas that extends the short-term projections in OECD Economic Outlook No. 93 of May 2013 to 2020 suggests that in the absence of policy adjustments beyond 2014 international imbalances could rebound as output gaps gradually close and housing markets normalise, though to levels below the pre-crisis peak. Ambitious fiscal adjustment in countries with the largest remaining fiscal imbalances and selected structural reforms could offset the cyclical rebound in international imbalances and prevent diverging net asset positions in most areas. Moreover, ambitious fiscal and structural policy adjustments would provide some margin in case upside risks to international imbalances -- such as renewed housing booms that could be triggered by a rebound in cross-border capital flows or higher oil prices -- materialise
Keywords: Economics